On shifting grounds analysing the shifting and transferring patterns of UP Journalism students - Peralta, Lea Kathrine Battung 1990- (Quezon City College of Mass Communication, University of the Philippines Diliman, 2016)
"This study analyzes the shifting and transferring patterns of UP Journalism students from 2010-2015. It also determines the reasons students have for shifting or transferring into the Journalism program, or for shifting out of the program. Furthermore, this study looks at the perception of shiftees and transferees on the Journalism curriculum of the UP College of Mass Communication. The UP College of Mass Communication Administration Office provided data for the number of shiftees and transferees during the five-year range while survey and in-depth interviews gathered from 116 respondents determined the reasons for shifting or transferring and the perception of the students to the course. Results show that students take into consideration the most the pursuit of their passion as well as their parents recommendation of courses/career tracks in their shifting decisions."
Vita.
Thesis (A.B. Journalism)--University of the Philippines Diliman